TREN TRANSFORMASI ASESMEN SPIRITUALITAS DALAM PENDIDIKAN ISLAM BERBASIS DIGITAL PORTFOLIO: A SYSTEMATIC LITERATURE REVIEW - Fadhila Nur Azizah; Prisca Anggun Ferian Putri; Chusnul Chotimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The transformation of spirituality assessment in Islamic education toward a digital portfolio approach has become a central issue in affective evaluation still faces various methodological challenges, such as social desirability bias and the lack of data triangulation. This study aims to analyze trends in the use of affective assessment instruments and identify gaps in the transformation toward more integrative and digital approaches. The method used is a Systematic Literature Review (SLR) following the Kitchenham & Charters guidelines. Article searches were conducted through Google Scholar, GARUDA, SINTA, and DOAJ databases for the period 2015–2025. From 200 initial articles, 25 articles met the inclusion criteria and were analyzed. The results show that (1) Likert scales in self-report instruments remain dominant, (2) the use of direct observation and peer assessment remains very limited, (3) no affective evaluation model integrating all three approaches has been identified, and (4) the transformation toward digital assessment is still in its early stages. This study recommends the development of an integrated affective assessment model based on triangulation and digitalization as a direction for future transformation